Markedly clinical improvement of papulopustular rosacea with multimodality therapeutic approach: a case report - Priyanto, Mufqi Handaru; Wardani, Amanda Nandi; Legiawati, Lili; Sitohang, Irma Bernadette Simbolon; Suseno, Lis Surachmiati (Explorer Front, 2023)
Introduction: Rosacea is a chronic inflammatory skin disease that mainly affects the central area of the face. There are four subtypes, and they may progress between subtypes or span multiple subtypes. Due to its long course of the disease, optimum treatments are needed to control the disease progression. Case: We reported rapid improvement of combining topical metronidazole, doxycycline, and light emitting diode for treating a patient with papulopustular rosacea in a 44-years-old woman, a week from the initial therapy. Discussion: Therapeutic approaches to rosacea mainly focus on controlling the symptoms with anti-inflammatory agents. More recently, photodynamic therapy, especially light-emitting diodes, has been introduced as a valid alternative or an adjuvant therapy to conventional treatment through their synergic mechanism between therapeutic modalities. Conclusions: This combination treatment may be effective for treating papulopustular rosacea without any side effects.